Poster 233: The Presence of a Jumping J-Sign is Driven Primarily by Trochlear Factors and not Patella Alta or TT-TG Distance. Issue 7 (30th July 2022) - Hevesi, Mario; Cregar, William; Zavras, Athan; Trasolini, Nicholas; Yanke, Adam; Dandu, Navya
Objectives: The J-sign is a commonly utilized physical exam measurement in the assessment of a patellar instability patient. A severe preoperative J-sign, classified as a "jumping J sign", has demonstrated associations with poorer short-term postoperative outcomes, and a jumping quality may persist as a bothersome symptom even after successful stabilization. Successful surgical treatment requires an understanding of the anatomic drivers of the jumping quality of a J-sign. Therefore, the objective of this study is to determine the underlying anatomic factors which contribute to a jumping J-sign. Methods: All patients undergoing evaluation for patellar instability at a single institution between 2013-2021 with an available knee MRI were included. Patients with a prior history of knee surgery were excluded. The presence of a jumping J-sign and its relationship to patellofemoral measures including Caton Deschamps Index (CDI), trochlear dysplasia, tibial tubercle to trochlear groove distance (TT-TG), tibial tubercle lateralization, coronal mechanical axis, trochlear bump height, and knee rotation angle were recorded based on measurements using standardized 1.5T MRIs. Statistical analysis was performed in RStudio (software version 4.1.0, R Foundation for Statistical Computing, Vienna, Austria). Results: 67 patients met inclusion criteria (42 female, 25 male, age: 20.3±8.2 years) and were evaluated. Thirteen patients (19%) demonstrated a jumping J-sign on physical exam. On univariate analysis, increasing CDI (Odds Ratio [OR] increase of 1.5 per 0.1 increase in CDI, p=0.048) and increasing trochlear bump height (1.7 OR increase per mm bump height) were significantly associated with a jumping J-sign. Additionally, a jumping J-sign was associated with the presence of Dejour A (Odds Ratio [OR]: 1.1, p=0.02) and Dejour B (OR: 2.4, p<0.01) but not Dejour C (p=0.14) or D (p>0.99) trochlear dysplasia. In contrast, TT-TG, tubercle lateralization, mechanical axis, and knee rotation angle were not significant drivers of a jumping J-sign (p³0.17). On multivariate analysis, Dejour A (OR: 1.25, p=0.04) and Dejour B (OR: 1.4, p<0.01) trochlear dysplasia as well as trochlear bump height (1.09 OR increase per mm bump height, p=0.01) were significantly associated with a jumping J-sign. Patella alta was not associated with a jumping J-sign after accounting for trochlear dysplasia and bump height (OR: 1.04, p=0.12). Conclusions: The presence of a jumping J-sign is determined by the interaction of trochlear dysplasia and bump height. While patients with increasing degrees of patella alta demonstrate an increased incidence of a jumping J-sign, this physical exam finding has a multifactorial etiology and is driven primarily by correlation with underlying trochlear factors including dysplasia.